Management of pediatric portal vein cavernous transformation: a seven-case single-center study - Chen, Zhida; Liu, Hui; Li, Wanfu; Maimaiti, Gulimiremu; Maimaijiang, Ayiguzaili; Jiayilawu, Yeliaman; Habuding, Aerxin; Xi, Runqi; Wang, Haoyu; Huxitaer, Halimulati; Song, FangJuan (Frontiers in Pediatrics, 2025)
BackgroundCavernous transformation of the portal vein (CTPV) is one of the significant pathogenic factors of prehepatic portal hypertension in children. The Rex shunt, by reconstructing an intrahepatic portal venous pathway, not only effectively reduces portal pressure and restores physiological hepatic blood flow, but also promotes normal growth and development, making it the treatment of choice for CTPV. In contrast, traditional non-selective shunting procedures primarily alleviate symptoms of portal hypertension without restoring hepatic perfusion, thereby compromising growth potential. For patients unsuitable for the Rex shunt, living donor liver transplantation provides a definitive cure. Overall, both the Rex shunt and liver transplantation improve long-term outcomes in children with CTPV by reestablishing physiological portal circulation.PurposeThis study aims to summarize the clinical efficacy and institutional experience in the management of pediatric portal vein cavernous transformation.MethodsA retrospective analysis was conducted on seven children with portal vein cavernous transformation treated at the Department of Pediatric Surgery, First Affiliated Hospital of Xinjiang Medical University, between December 2021 and March 2025. The cohort included four boys and three girls, with ages ranging from 5 years and 10 months to 12 years. All patients had a history of esophagogastric variceal bleeding and hypersplenism. Preoperative evaluations included portal vein color Doppler ultrasonography, abdominal computed tomography angiography (CTA) to assess the portal venous system anatomy and blood flow dynamics. Following a rigorous assessment, six patients underwent living donor liver transplantation, and one patient underwent Rex shunt surgery.ResultsAll seven surgeries were successfully completed. During a follow-up period ranging from 3 to 42 months, no episodes of gastrointestinal bleeding were observed in any patient. Among the six patients who underwent liver transplantation, no cases of graft rejection, arterial complications, or biliary complications were reported. Postoperatively, all seven patients demonstrated a significant reduction in portal vein pressure and improvement in pancytopenia compared to preoperative values (P < 0.05).Of the six transplant recipients, three required portal vein reconstruction using allogeneic vascular grafts to establish continuity between the graft portal vein and the recipient superior mesenteric vein; in two cases, direct anastomosis was performed between the graft portal vein and a suitable segment of the recipient portal vein. The patient who underwent Rex shunt surgery received autologous inferior mesenteric vein grafting to reconstruct the portal pathway. Three transplant recipients developed portal vein anastomotic stenosis postoperatively, all of which were successfully managed with a single session of portal venography combined with balloon angioplasty.ConclusionsWhile the Rex shunt remains the gold standard for the treatment of portal vein cavernous transformation, living donor liver transplantation provides a viable alternative for patients unsuitable for Rex shunt reconstruction.